The depiction of Muslims in contemporary Latin narratives of the First Crusade - Bourke, Yan (Trinity College (Dublin, Ireland). Department of History, 2017)
Although they undoubtedly drew on knowledge that existed in Western Europe, the authors of histories the First Crusade lacked an authoritative source on Islam. As such, in trying to give more complete depictions of Muslims, authors of crusade accounts for the most part were free to create images of their own, picking and choosing between elements of various available models and their own observations. This dissertation is concerned with their attempts to cope with the task of explaining the phenomeon of Islam and the character of Muslims to their audience. Lacking an authority on the nature of Islam on which to rely, and influenced by their different intellectual backgrounds, experiences and their own interpretations of the crusade itself, these attempts to explain Islam varied considerably from author to author. Though there have been a number of works published around the subject of the image of Islam in the West, none has taken the approach of this study. Many have focussed more on the accuracy of the image than on a close analysis of what it meant to contemporaries and how it was derived. Most have also tended to analyse only a few sources deemed representative, over a long period of time. This approach does not give enough attention to the great degree of variation between the First Crusade sources and the individuality of the authors of the accounts in their depictions of Muslims. This thesis will conduct a minute investigation of the language used by the authors to deal with Islam and the culture and manners of Muslims with an emphasis on identifying the ways in which they differed from one another.
Keywords: History, Ph.D.; PhD Trinity College Dublin, 2017